Transintegration of Customary Law and Sharia: Lesson from Historical Law and Cultural Law - Subhan, Subhan; Rahman, Fuad; Alfikri, Albert (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2024)
This study explores the transintegration of customary law and Islamic law in Jambi in the context of history and culture. With a descriptive qualitative approach, this study uses data collection methods: in-depth interviews with traditional figures, ulama, and the community, field observations, and analysis of historical documents and related legal regulations. Data analysis techniques are carried out by identifying patterns, themes, and changes in the relationship between customary law and sharia. The study results indicate that the integration of customary law and sharia in Jambi has been going on since the time of the Jambi Sultanate, with the important role of figures such as Datuk Orang Kayo Hitam. In family law, Jambi customs accommodate sharia principles such as the prohibition of marrying siblings, although there are differences in specific customary rules. In criminal law, the application of qisas is adapted into customary fines, reflecting an effort to compromise sharia values ​​in the structure of customary law. The challenges of modernization and plurality create dynamics in maintaining the principle of